2021
DOI: 10.1016/j.joep.2020.102348
|View full text |Cite
|
Sign up to set email alerts
|

Making the carbon basket count: Goal setting promotes sustainable consumption in a simulated online supermarket

Abstract: We compared the effectiveness of basket goal-setting to product information strategies on sustainable consumption in a simulated online supermarket. Experiment 1 found a significant effect of basket goal setting techniques with carbon basket feedback in either numerical or graphical form on the carbon content of baskets purchased but no effect of numerical product information alone or in combination with basket CO2 information. Experiment 2 also found that basket goal setting was effective, but found no additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…In addition, different consumer groups may respond to ecolabels in different ways [10]. Moreover, while studies have shown ecolabels to be effective at altering food purchasing or selection, these have often featured in relatively small numbers of products and/or participants, limiting the ability to examine effectiveness across the basket and different demographic groups [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different consumer groups may respond to ecolabels in different ways [10]. Moreover, while studies have shown ecolabels to be effective at altering food purchasing or selection, these have often featured in relatively small numbers of products and/or participants, limiting the ability to examine effectiveness across the basket and different demographic groups [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Even for products in a relatively narrow product category that were chosen to be comparable to each other, characteristics other than position and price play important roles in determining the purchasing decisions. Research has pointed out the importance of habits and taste in food choices (Fox et al, 2021;Osman & Jenkins, 2021;Riet et al, 2011); our results show that such habits might be too ingrained to be changed by subtle modification of situational cues, and more explicit interventions such as giving consumers carbon targets for their baskets as done in Kanay et al (2021) might be needed.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, carbon labels changed behavior in a small choice set (Vanclay et al 2011), while traffic-light and kilometric labels (which report GHG in terms of kilometers driven by a car) on individual products successfully reduced the carbon footprint in a small experimental online supermarket (Muller, Lacroix, and Ruffieux 2019). Similarly, the use of color-coded feedback on the carbon footprint of a basket successfully reduces the total GHG purchased (Kanay et al 2021).…”
Section: Retail Interventions To Promote Sustainable Consumptionmentioning
confidence: 99%